The negative impact of globalization on the religious, social and moral values of students of the Faculty of Education, University of Nyala, Sudan - Haroun, Mohamed Jibril Fadel; Abdel Rahman, Abdel Qadeem Abd Allah; Abdel Rahman, Gamal El Daban Ibrahim (Journal of Humanities & Social Sciences, 2017)
This study explored the negative impact of globalization on religious, social and moral values on students at the Faculty of Education, University of Nyala, Sudan The researchers adopted the descriptive, analytical and comparative methodologies to conduct this study, the study has arrived at important results that unveiled the negative impact on religious values at 77%.The study told the negative impact of globalization on social values on students at 70%, in addition to the effect on moral values at 82%.The most significant recommendations:  Reducing of watching T.V hours, resorting to Qur’an and Sunni, as basic sources for good conduct, guarding the student’s behavior and not allowing them wasting their time watching T.V channels and films which deviate them from moral values.
Keywords: the negative impact of globalization; values (religious, social, moral); students of the Faculty of Education; Nyala University; Sudan